The association of childhood trauma with sleep disturbances and risk of suicide in US veterans. (April 2021) - Alter, Sharon; Wilson, Caroline; Sun, Shengnan; Harris, Rachel E.; Wang, Zhaoyu; Vitale, Amanda; Hazlett, Erin A.; Goodman, Marianne; Ge, Yongchao; Yehuda, Rachel; Galfalvy, Hanga; Haghighi, Fatemeh
Abstract: Background: Sleep dysregulation is prevalent among veterans and is associated with increased risk of suicidal ideation and behaviors. A confluence of risk factors have been identified to date that contribute to increase risk for suicidal behavior. How these risk factors including childhood trauma, comorbid psychopathology, impulsivity, and hostility together with sleep disturbance contribute to suicide risk remains an open question. These factors have never been examined simultaneously in a unified mediation model, as investigated in the present study, to determine their relative contribution to suicide risk. Methods: Veterans (N = 105) were recruited across 3-groups, including Major Depressive Disorder (MDD) with/without a history of a suicide attempt (n = 35 and n = 37, respectively), and non-psychiatric controls, who had no history of mental illness or suicidal behavior (n = 33). The participants were assessed using validated self-report assessments with in-depth phenotyping for relevant risk factors associated with suicidal behavior including childhood adversity, depression severity, impulsivity, hostility, and sleep quality. These factors were included in mediation models using path analysis. Results: Across all subjects including those with MDD and non-psychiatric controls, mediation analysis showed that higher levels of childhood trauma had an indirect effect on poor sleep quality (p = 0.001). This effect was orthogonal, being independently mediated by both MDD psychopathology (p = 0.003), and higher traits of impulsivity (p = 0.001) and hostility (p = 0.015). Amongst MDD veterans, childhood trauma was directly associated with increased suicide risk (p = 0.034), irrespective of their severity of depression, or their degree of hostility and impulsivity. Limitations: include use of self-report data, and the inability to establish causal inferences with cross-sectional design. Conclusion: Childhood adversity as a significant pre-deployment risk factor for disturbed sleep and elevated suicide risk, potentially important for incorporation in clinical practice for suicide. Highlights: Childhood trauma contributes to increased risk of sleep disturbance exacerbated by military service The effect of childhood trauma on sleep disturbance is mediated by depression psychopathology, impulsivity, and hostility Evaluation of childhood trauma as a pre-deployment risk factor for suicide needs to be incorporated in suicide prevention